Wayang Kulit as Diplomacy of Javanese Values at the Community Level: A Study of Local Performances in Blitar and Tulungagung - Adiyanto, Adiyanto; Ariadi, Septi; Setiajiningrum, Erna (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to analyze the role of wayang kulit as a medium of cultural diplomacy at the community level with case studies in Blitar and Tulungagung Regencies, East Java. The purpose of the research is to identify the adaptation strategy of wayang kulit in maintaining its relevance in the modern era as well as uncovering the mechanism of transmission of Javanese values through this traditional performance. The research used a qualitative approach with ethnographic methods, including observation of 15 puppet performances, in-depth interviews with 12 key informants (puppeteers, audiences, and policy makers), and analysis of play script documents and performance recordings. The results of the study revealed three main findings: (1) Wayang kulit functions effectively as a space for value diplomacy through the creative adaptation of puppeteers in inserting contemporary messages; (2) There is a significant generation gap with only 18% of the audience being young (15-25 years old), but digital innovations such as short film content on social media platforms have emerged; (3) A shift in the creative economy model where 60% of the income of wayang groups now comes from institutional sponsorships. The novelty of this research lies in the development of the "Wayang Diplomacy 4.0" model that integrates the preservation of traditional values with digital adaptation and the strengthening of the creative economy, as well as findings on the role of performance liminality as a medium for local conflict resolution. The findings of this study make an important contribution to the development of community-based theory of cultural diplomacy and offer practical recommendations for policymakers in the preservation of traditional arts. This research expands the academic discourse on soft power culture by showing its application to non-state actors at the local level, while providing empirical evidence on the cultural resilience of the people of East Java in responding to the changing times.